EFFECT OF SEED SOAKING WITH A GROWTH REGULATOR (ATONIK) AND SEEDING DATES ON THE VEGETATIVE GROWTH CHARACTERISTICS OF SORGHUM BICOLOR L. - Nihad M. Abood,; Shakir S. Mirare, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was carried out during the spring and fall seasons of 2021 at Al-Hamidiya Research Station of the College of Agriculture, With the aim of studying the effect of soaking seeds with Atonik growth regulator and seeding dates on growth characteristics and plant nutrients content for three varieties of sorghum. A randomized complete block design with split-split plot arrangement was used with three replications. The main plot included seeding dates for both spring and fall seasons, while the sub-plot included the concentrations of the growth regulator (Atonk) which are 0-, 2.5- and 5-ml L-1, while the three varieties (Inqath, Lelu and Giza 113) were allocated to the sub-sub plots. The results showed the superiority of the cultivar Inqath in most of the studied traits such as leaf area, plant content of chlorophyll and plant content of potassium, phosphorous and nitrogen (4406, 3888 cm2 and 58.36 59.17 spad) for both seasons, respectively. Whereas, Giza 113 cultivar outperformed in terms of plant height for both seasons. The plants which seeds soaked at a concentration of 5 ml L-1 also outperformed in all studied traits seeding date had a significant effects for both seasons. The interaction between the studied factors had a significant effect for most of the traits.